High-density lipoprotein subfractions and influence of endothelial lipase in a healthy Turkish population: A study in a land of low high-density lipoprotein cholesterol. (June 2014) - Kilic, Harun; Atalar, Enver; Lay, Incilay; Yazihan, Nuray; Buyukcam, Fatih; Saygisunar, Ugur; Aksoy, Murat; Gunduz, Huseyin; Akdemir, Ramazan
Abstract Purpose. Low concentration of high-density lipoprotein (HDL) is prevalent in Turkey. Endothelial lipase (EL) regulates lipoprotein metabolism. Small, lipid-poor HDL particles represent more-efficient cholesterol acceptors than their large, lipid-rich counterparts. The aim of this study was to investigate HDL subfractions and the effect of EL on HDL concentrations in healthy Turkish population. Methods. 102 healthy subjects were included in the study (mean age 33.6 ± 10.3 years, 42 female). HDL subfractions were assayed by single precipitation method and EL concentrations were measured by competitive enzyme immunoassay. Results. Mean HDL concentrations were 1.45 ± 0.37 mmol/L in women, 1.10 ± 0.30 mmol/L in men. Small HDL subfraction levels did not differ statistically between < 1 mmol/L and ≥ 1.6 mmol/L total HDL groups. Small HDL was not correlated with EL, low density lipoprotein cholesterol (LDL), triglyceride (TG) and age but positively correlated with total cholesterol and HDL (r = 0.2, p = 0.017; r = 0.2, p = 0.028, respectively). Large HDL was not correlated with age, EL and total cholesterol, and negatively correlated with HDL, LDL, TG (r = − 0.7, p < 0.001; r = − 0.2, p = 0.045; r = − 0.3, p < 0.001, respectively). If subjects were divided into two groups as HDL< 1 mmol/L and HDL > 1.6 mmol/L, mean EL concentrations were 475.83 ± 521.77 nmol/L and 529.71 ± 276.92 nmol/L, respectively (p = 0.086). Conclusion. There were no differences between small HDL concentrations in the HDL low and high groups. Our data did not support EL to be the reason for low HDL in a healthy Turkish population. Our results in a healthy population may serve as a reference for clinical studies on HDL subfractions.